Antibiogram of bacteria isolated from the peritoneal fluid of uterine torsion affected buffaloes - BRAR, P S; SINGH, H; SHARMA, D K; NANDA, A S (The Indian Journal of Animal Reproduction, 2007)
The present study was conducted to isolate bacteria from peritoneal fluid of buffaloes suffering fromuterine torsion and determine sensitivity pattern to 16 commonly used antimicrobials. The peritonealfluid from 15 buffaloes suffering from uterine torsion was collected aseptically, and was processedfor bacterial isolation and in-vitro antibiotic sensitivity test using standard disc diffusion technique.The Pseudomonas spp (n=4) and Staph. aureus (n=4) were the most predominant bacteria isolatedfrom the peritoneal fluid followed by Staph.epidermicus (n=3). Most of the isolates were sensitive toGentamicin (93.33%), followed by Furandantin (80%), Chloramphenicol (73.34%), Furazolidone(66.67%), whereas more than half the isolates (n=8) were resistant to Kanamycin (53.34%),Streptomycin (60%), Cephaloridine (66.66%), Co-Trimoxazole (53.34%) and Nalidixic Acid (53.34%)and all the isolates were resistantto Pencillin-G. This study indicates the presence ofbacterial infectionin the peritoneal fluid of buffaloes suffering from uterine torsion and that culture and sensitivity ofperitoneal fluid should be carried out for rational treatment of peritonitis in such animals.
Keywords: Buffalo; Peritoneal fluid; Bacterial isolates